Effectiveness of Fly Ash, Dolomite, and Organic Fertilizers in Enhancing Oil Palm Seedling Growth - Pramudya, Yudhi; Hanum, Farrah Fadhillah; Muhammad, Azrian Makmum; Wardhana, Budi Setya; Pamungkas, Saktiyono Sigit Tri (Journal of Applied Agricultural Science and Technology, 2025)
Oil Palm (Elaeis guineensis Jacq.) is a crucial plantation commodity in Indonesia's economy. The increasing global demand for oil palm has driven the expansion of oil palm plantations. However, this expansion is often constrained by limited fertile land. Fly ash, a byproduct of coal combustion, contains essential nutrients such as calcium, magnesium, and silica. Several studies suggest that fly ash potentially improves soil physical and chemical properties, as well as enhance nutrient availability for plants. This research aims to evaluate the effectiveness of adding fly ash in various growing media, dolomite, and organic fertilizers on the growth of oil palm seedlings. The study employs a Completely Randomized Design (CRD) with several treatment combinations, including fly ash, organic fertilizer, dolomite, and NPK 16:16:16 fertilizer doses. The results indicate that combining fly ash and organic fertilizer is the best choice for improving oil palm seedling growth. Additionally, adding NPK 16:16:16 fertilizer at 36 grams per polybag yields excellent growth results. Interaction analysis indicates significant effects of these combinations on seedling growth improvement. This preliminary study is expected to provide foundational information useful for further research on utilizing fly ash and other organic materials in oil palm cultivation and the potential application of this technology on a larger scale.